Using Simulated Patients to Understand Non-Prescription Antibiotic Dispensing in Indonesia: A Systematic Review - Fathul Muin; Anna Wahyuni Widayanti (Universitas Airlangga, 2023)
Background: Dispensing antibiotics without a prescription at community pharmacies is a significant contributor to the ongoing global public health issue of antibiotic resistance. Objectives: To estimate the proportion of antibiotics that are dispensed without a prescription in community pharmacies in various Indonesian cities. Methods: A literature review was conducted via PubMed, Science Direct, Google Scholar, Garuda, and Neliti for articles published between January 2007 and December 2022 combined with Boolean operators. The literature search keywords were (simulated patientsOR mystery shopper OR sample patients OR dummy patients) AND (